2015
DOI: 10.1002/pssr.201510244
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of polycrystalline graphene membranes by in situ nanoindentation in a scanning electron microscope

Abstract: Failure of polycrystalline graphene grown by chemical vapor deposition was investigated by nanoindentation in a scanning electron microscope. Circular graphene membranes were subject to central point loads using a nanomanipulator combined with an atomic force microscope cantilever as a force sensor. The grain boundaries of the polycrystalline graphene were visualized by Raman spectroscopy coupled with a carbon isotope labeling technique. Graphene membranes without any grain boundary had a failure strength of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…We note that even though our simulations are for nanocrystalline grains, we expect our results to be valid for much larger micrometer-sized grains, since no new physics is expected to emerge at the intermediate length scales. Our results are consistent with the observations that presence of GB reduces the strength of polycrystalline graphene 20 21 . Finally, we note that our simulations consider only the equilibrium geometrically necessary dislocations, and ignore the non-equilibrium defects such as disclinations 57 58 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We note that even though our simulations are for nanocrystalline grains, we expect our results to be valid for much larger micrometer-sized grains, since no new physics is expected to emerge at the intermediate length scales. Our results are consistent with the observations that presence of GB reduces the strength of polycrystalline graphene 20 21 . Finally, we note that our simulations consider only the equilibrium geometrically necessary dislocations, and ignore the non-equilibrium defects such as disclinations 57 58 .…”
Section: Discussionsupporting
confidence: 93%
“…In most materials, these properties tend to be mutually exclusive 18 . There are conflicting experimental reports whether the strength of polycrystalline graphene is actually a function of grain size 19 20 21 making the role of simulation and theory more critical. Understanding these statistical fluctuations has become important in light of the fact that graphene synthesized with chemical vapour deposition (CVD) is polycrystalline, and this method is being used to manufacture more than 300,000 m 2 of graphene annually 22 23 .…”
mentioning
confidence: 99%
“…These values for exfoliated graphene are smaller than the Young's modulus of 1 TPa and maximum stress of 130 GPa obtained from AFM indentation experiments and other authors (Lee et al 2008). This result is consistent with previous reports that fractured graphene exhibits diminished mechanical properties (Suk et al 2015). We are conducting further research into the S-S curve interpretation of few-layer exfoliated graphene, as well as into the possibility of achieving wrinkle-free exfoliated graphene on the PTP device or enabling the transfer of exfoliated graphene in a monolayer or bilayer.…”
Section: Resultssupporting
confidence: 93%
“…The fracture strengths in the study by Kotakoski and Meyer [90] and the paper of Yang et al [94], however, showed no significant dependence on grain size. Nanoindentation measurements by Suk et al [111] give support to a decreased fracture strength of polycrystalline graphene, with the fracture strength being smaller for smaller grains. For the comparison between theory and experiment, it is again worth pointing out that most numerical studies havẽ …”
Section: Fracture Strengthmentioning
confidence: 98%